Conceptual and Logical Model for Vehicle Insurance Management System: Case Study at Insurance Company, Libya - Yousif, Ramdan S.M.A. (2010)
This project intended to design a conceptual and logical model of Vehicle Insurance Management System for Insurance Company. The System will use client server system to run daily operations and able to smooth up the daily operation and reduce the operation cost as well. Prior to the development of the system, a study has been done so that the organization can gain real benefits from adopting a suitable Vehicle Insurance System. So, a Conceptual and Logical Model of the system has been made to simulate the model to determine the effectiveness of the system. The prototype will be developed know as Libya Insurance Company Vehicle Insurance Management System (LICVIMS). LICVIMS able to control the daily Vehicle Insurance transaction and also management system.